Macrophage Polarization Modulates FcγR- and CD13-Mediated Phagocytosis and Reactive Oxygen Species Production, Independently of Receptor Membrane Expression - Mendoza-Coronel, Elizabeth; Ortega, Enrique (Frontiers in Immunology, 2017)
In response to microenvironmental cues, macrophages undergo a profound phenotypic transformation acquiring distinct activation phenotypes ranging from proinflammatory (M1) to anti-inflammatory (M2). To study how activation phenotype influences phagocytosis and production of reactive oxygen species (ROS) mediated by receptors for IgG antibodies (Fc receptors) and by CD13, human monocyte-derived macrophages were polarized to distinct phenotypes using IFN-gamma(Mph-IFNγ), IL-4 (Mph-IL-4), or IL-10 (Mph-IL-10). Phenotypically, Mph-IFNγ were characterized as CD14+CD80+CD86+ cells, Mph-IL-4 as CD209highCD206+CD11b+CD14low, and Mph-IL10 as CD16+CD163+ cells. As compared to non-polarized macrophages, FcgRI expression increased in Mph-IFNγ and Mph-IL10, and FcgRIII expression increased in Mph-IL-10. None of the polarizing cytokines modified FcgRII or CD13 expression. Functionally, we found that cytokine-mediated activation significantly and distinctively affected FcgR- and CD13-mediated phagocytosis and ROS generation. As compared to non-polarized macrophages, FcgRI-, FcgRII- and CD13-mediated phagocytosis was significantly increased in Mph-IL-10, and decreased in Mph-IFNγ, although both cytokines significantly upregulated FcgRI expression. IL-10 also increased phagocytosis of E. coli, showing that the effect of IL-10 on macrophage phagocytosis is not specific for a particular receptor. Interestingly, Mph-IL-4, which showed poor FcγR- and CD13-mediated phagocytosis, showed very high phagocytosis of E. coli and zymosan. Coupled with phagocytosis, macrophages produce ROS that contribute to microbial killing. As expected, Mph-IFNγ showed significant production of ROS after FcgRI-, FcgRII- or CD13-mediated phagocytosis. Unexpectedly, we found that Mph-IL-10 can also produce ROS after simultaneous stimulation through several phagocytic receptors, as coaggregation of FcgRI/FcgRII/CD13 induced a belated but significant ROS production. Together, these results demonstrate that activation of macrophages by each cytokine distinctly modulates expression of phagocytic receptors, FcgR- and CD13-mediated phagocytosis, and ROS production..